Actual state of cenopopulations of Stipa dasypfylla as an indicator of succession stages in steppe phytocenoses in natural reserves (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Density, age and spatial structures of cenopopulations of Stipa dasyphylla, one of the main tussock cenosoformative species of steppe phytocenoses, are researched in the south-east of Ukrainian. Actual state of S. dasyphylla populations may be used to apprise whole plant communities in natural reserves.
Keywords: age structure, indicator species, phytocenosis, spatial structure, steppe communities.